2009
DOI: 10.1021/ja903635y
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Phase Synthesis of Block Copolymers Containing Sequence-Ordered Segments

Abstract: Monodisperse sequence-defined oligomers have been synthesized in solution in the absence of protecting groups. These structures have been prepared stepwise using two consecutive chemoselective reactions: 1,3-dipolar cycloaddition of terminal alkynes and azides and amidification of carboxylic acids with primary amines. These oligomers were efficiently constructed on either a conventional solid support (commercial Wang resin) or tailor-made soluble polystyrene supports synthesized by atom-transfer radical polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
150
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(152 citation statements)
references
References 30 publications
0
150
0
2
Order By: Relevance
“…[11,13] Iterative synthetic approaches (e.g., solid-phase synthesis) allow the design of short sequence-defined oligomers; however these technically demanding syntheses remain unfortunately marginal in synthetic polymer science. [4,[13][14][15] Besides, one-pot polymerization processes such as step-growth or chain-growth polymerizations offer very limited options for controlling macromolecular sequences. [11] Indeed, in these conventional synthetic approaches, polymer chains are assembled in a concentrated ''soup'' of comonomers, and thus statistics govern the copolymerization processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,13] Iterative synthetic approaches (e.g., solid-phase synthesis) allow the design of short sequence-defined oligomers; however these technically demanding syntheses remain unfortunately marginal in synthetic polymer science. [4,[13][14][15] Besides, one-pot polymerization processes such as step-growth or chain-growth polymerizations offer very limited options for controlling macromolecular sequences. [11] Indeed, in these conventional synthetic approaches, polymer chains are assembled in a concentrated ''soup'' of comonomers, and thus statistics govern the copolymerization processes.…”
Section: Introductionmentioning
confidence: 99%
“…[5,13,15,20,[22][23][24][25][26][27][28][29][30][31][32] In particular, a few research groups investigated sequence-regulation in chaingrowths polymerizations. For instance, the innovative approaches recently reported by the research groups of Sawamoto, [26,29,32,33] Thomas, [10,27] and Kamigaito [20,30] have to be mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Other unique approaches include a-olefins-alt-ethylene copolymerization using bridged C 1 -symmetric metallocenes with heterotopic coordination sites, [12] ring-opening insertion metathesis polymerization, [13] and solid or liquid-phase iterative synthesis. [14] In order to obtain alternating polymers, coordination polymerization using well-defined metal complexes has played a leading role in the last two decades. The goal of the proposed paper is the description of catalysts that allow higher order sequence control of this latter type, and create alternating macromolecular structures with advanced properties.…”
Section: Introductionmentioning
confidence: 99%
“…Site-selective coordination also seems to occur with the C 1 -symmetric pyridine-oxazoline ligand used, causing syndiotactic copolymerization as was the case in the original catalytic system containing bipyridine. [57] Nozaki et al have demonstrated that a cationic Pd(II) complex of unsymmetrical chiral bidentate phosphinephosphite, (R,S)-BINAPHOS (14), serves as an efficient catalyst for the asymmetric copolymerization of TBS with carbon ligands. Even if 2,1-insertion takes place, rapid b-hydride elimination occurs, as is common with the other phosphorus ligands, but in that case the resulting Pd-H species reinitiates the copolymerization, as was proven by MALDI-TOF mass analysis of the product copolymers.…”
mentioning
confidence: 99%
“…Lutz and coworkers [20,80] developed solid phase synthesis using modified Wang resin in combination with orthogonal coupling reactions such as azide alkyne cycloaddi-…”
Section: Solid Phase Synthesis and Iterative Strategymentioning
confidence: 99%